2013
DOI: 10.3727/096368912x637019
|View full text |Cite
|
Sign up to set email alerts
|

Neural Induction with Neurogenin 1 Enhances the Therapeutic Potential of Mesenchymal Stem Cells in an Amyotrophic Lateral Sclerosis Mouse Model

Abstract: Amyotrophic lateral sclerosis (ALS) is characterized by progressive dysfunction and degeneration of motor neurons in the central nervous system (CNS). In the absence of effective drug treatments for ALS, stem cell treatment has emerged as a candidate therapy for this disease. To date, however, there is no consensus protocol that stipulates stem cell types, transplantation timing, or frequency. Using an ALS mouse model carrying a high copy number of a mutant human superoxide dismutase-1 (SOD1)(G93A) transgene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 75 publications
1
30
1
Order By: Relevance
“…Corner test is used to detect unilateral abnormalities of sensory and motor functions in the stroke model [17]. Corner was made by placing two wooden cardboards (30 cm × 20 cm × 1 cm) at an angle of 30 degree.…”
Section: Methodsmentioning
confidence: 99%
“…Corner test is used to detect unilateral abnormalities of sensory and motor functions in the stroke model [17]. Corner was made by placing two wooden cardboards (30 cm × 20 cm × 1 cm) at an angle of 30 degree.…”
Section: Methodsmentioning
confidence: 99%
“…A recent in vivo study induced in MSCs overexpression of neurogenin 1(Ngn1), a transcriptional regulator that plays a role in initiating neuronal differentiation. It was found that transplantation of MSCs-Ngn1 improved MN survival in SOD1 mice but that transplantation of unprocessed MSCs did not [25]. Although no evidence that MSC-Ngn1 cells had differentiated into neuronal cells was presented, this study did show the increased ability of MSC-Ngn1 cells to migrate to the spinal cord compared to unmodified MSCs.…”
Section: Therapeutic Applications Of Mesenchymal Stem Cells For Amyotmentioning
confidence: 60%
“…In preclinical studies, MSCs administered intravenously into SOD1 mice resulted in cell migration to various peripheral tissues as well as to the brain and spinal cord [25,60-62]. Significant increase in life span and delay of disease progression were observed in two of these studies [60,61], and Uccelli and colleagues [61] suggest reduced microglia activation and reduced oxidative stress as potential mechanisms of repair.…”
Section: Treatment Strategy To Design Effective Therapymentioning
confidence: 99%
“…G93A-SOD mice receiving intraspinal MSC transplants exhibit favorable effects on neuroinflammation, astrogliosis and microgial activation [37]. Furthermore, induction of neural differentiation of MSCs via neurogenin 1 expression enhances MSC homing to the CNS following intravenous administration in ALS mice and is associated with delayed disease onset and improved motor function [38]. …”
Section: Preclinical Advances In Stem Cell Therapies For Alsmentioning
confidence: 99%